James Henthorn Todd, a Tractarian at Trinity : making Ireland in the mid-nineteenth century - Hanna, Patricia (McKee) (Irish School of Ecumenics, 2015)
In the following chapters I have created a biographical portrait of Todd as a Tractarian at Trinity College, Dublin and studied the variety and range of his texts which contributed to making Ireland in the mid-nineteenth century. In the first instance I have taken note of the argument that the Church of Ireland was little more than a ‘sect’ by the end of 1869, the year of Todd’s death. Analysis of eighteenth century political ideology, as preached in sermons, contributes to this view of ‘sect’-like thinking connected to the defence of the state and the mission to convert the native population to a minority church. I have taken up the idea that the introduction of a national system of education in 1831, at primary level, followed by his experience of founding a new Irish secondary school with friends, called St. Columba’s, and finally his contribution to the 1853 Government Report on Trinity, all generated a balanced and modest contribution to change, as seen in his texts and letters.
Keywords: Religions, Peace Studies & Theology, Ph.D.; Ph.D. Trinity College Dublin